The integration of zero-base budgeting with management-by-objectives: An empirical inquiry - Williams, John J.; Newton, James D.; Morgan, Eric A. (Accounting, Organizations and Society, 1985)
Popular arguments in the management literature advocate the implementation congruity and complementarity of zero-base budgeting (ZBB) with an established management-by-objectives (MBO) system. The present study examined management perceptions on 28 ZBB implementation variables for MBO users and non-MBO users which were gathered from 153 managers at two hierarchical levels within a single private sector organization. Results from both univariate and multivariate tests indicate that ZBB implementation was not facilitated by the existence of an MBO system for either lower level management or for upper level management. The evidence obtained here strongly suggests that the purported conventional rationale underlying ZBB coupling with an extant MBO system is seriously defective; ZBB design implementation issues need to be thoroughly re-assessed, with the emphasis on matching compatible systemic properties between information sub-systems.